Asset prices, inflation and monetary control: Re-inventing money as a policy tool - Peter Spahn (Research On Money in the Economy (ROME), 2010)
Low inflation on goods markets provides no reliable precondition for asset-market stability; it might even promote the emergence of bubbles because interest rates and risk premia appear to be low. A further factor driving asset demand is easy availability of credit, which in turn roots in the banking system operating in a regime of endogenous central-bank money. A comparison of Bundesbank and ECB policies suggests that credit growth can be controlled more efficiently if rising interest rates are accompanied by some liquidity squeeze that supports the spillover of a monetary restriction to capital markets. The announcement effect of a central bank Charter including the goal of financial-market stability helps to deter private agents from excessive asset trading.
Keywords: E5; 330; Open market policy; asset price bubble; euro money market; ECB strategy